Thienopyridines in cardiovascular disease: Focus on Clopidogrel resistance - Siller-Matula, Jolanta; Schrör, Karsten; Wojta, Johann; Huber, Kurt (Thrombosis and Haemostasis, 2007)
Platelets play an important role in atherothrombotic disease, as well as in the pathogenesis of atherosclerosis and in complications. Antiplatelet therapy with Clopidogrel represents at present an important treatment of coronary artery disease (CAD), especially in and after acute coronary syndromes (ACS), and after coronary interventions when stents are used. Clopidogrel is a potent and specific inhibitor of platelet ADP receptor (P2Y12 receptor) with high antithrombotic activity. Emerging data suggest that a significant percentage of individuals treated with Clopidogrel do not receive the expected therapeutic benefit because of a decreased responsiveness of their platelets, which is caused by several extrinsic and/or intrinsic mechanisms. As long as Clopidogrel is the “gold standard” in combination with aspirin in the treatment of patients undergoing percutaneous coronary intervention and stent implantation, the overall challenge is to develop a fast “point-of-care” assay to detect Clopidogrel resistance early and to enable alternative antithrombotic strategies in non-responders or low-responders. This test should be easily performed (bedside) and reproducible, with a standardized definition of response, which is known to correlate with clinical outcomes. Unfortunately, such a test does not exist at present. As an alternative, new ADP receptor antagonists with better bioavailability and improved pharmacokinetics, e.g. intestinal reabsorption as an active drug or 1:1 conversion into an active metabolite thus reducing individual variations, are in development and have already found their way into clinical use in phase-3 trials. Prasugrel is one of the incoming new drugs with high expectations, but other agents might follow in the near future.
Keywords: ADP receptors; platelet pharmacology; Clopidogrel resistance